Study of the compressive strength and unit weight of specimens made from lahar sand and lahar sand derived materials - Celzo, Ma. Salvacion I.
Continuous work on lahar had been undertaken by different research groups in order to utilize the materials that had been considered a disaster to our country. This study primarily aims to contribute to the studies that were already done by introducing the method of separation in the lahar sand in order to produce new materials with the purpose application in the construction industry.